Valuing ecosystem services provided by land commons in India: Implications for research and policy - Sandhu, Harpinder; Zhang, Wei; Meinzen-Dick, Ruth S.; ElDidi, Hagar; Perveen, Saiqa; Sharma, Janvi; Kaur, Japneet; Priyadarshini, Pratiti (IOP Publishing, 2023)
Commons provide many ecosystem services that support the livelihoods of billions around the world. However, their contribution to people and the economy are rarely estimated in economic terms. Here, we estimate the economic contribution of the land-based commons in India, which cover 66.5 million hectares. We conducted a systematic literature review of publications between 1990 and 2020 and selected 161 peer-reviewed studies to develop an ecosystem services valuation database for India. We identified 34 ecosystem services from this database. We estimate that forest commons provide ecosystem services worth $2108 per ha per year. Culturable wastelands and permanent pastures, and other grazing lands provide $861 per ha per year each, and barren and unculturable lands provide $196 per ha per year. Using the value transfer method, the average value of ecosystem services provided by land commons in India is estimated at $90.5 billion per year (range $24 – 192 billion). This broad range reflects the status and condition of those commons. Based on the trends in the decline of land-based commons, we estimate the value of ecosystem services will decline to $68 billion by 2050: $750 million worth of ecosystem services can be lost each year over the next 30 years. This will have devastating implications for rural populations that depend on the commons for livelihoods and the delivery of critical ecosystem services. We highlight the need to use ecosystem services valuation in decision-making and policy to protect and sustainably manage commons in India.